Facile, environmentally friendly, cost effective and scalable production of few-layered graphene - Amiri, A.; Zubir, M.N.M.; Dimiev, A.M.; Teng, K.H.; Shanbedi, M.; Kazi, S.N.; Rozali, S. (Elsevier, 2017)
Commercialization of graphene is still one the biggest challenges in the carbon field despite the development of several methods for its production. The lack of simple, cost-effective and scalable methods for mass-production of graphene hampers its promotion to the market. Here, we propose a new method for large-scale production of mono- and few-layered graphene via liquid phase exfoliation with the use of wet ball milling in the presence of organic solvents at extremely low temperatures. The wet ball milling combined with the temperature modulated high surface energy solvents affords exfoliation of bulk graphite into graphenes in a fast, scalable, cost effective and environmentally friendly process. The thorough statistical analysis of as-prepared graphene flakes demonstrates that more than 61% of the flakes comprise less than 5 layers, while ∼14% of the flakes were monolayer graphene. Combined with the ∼30% yield of few-layer graphene out of the graphite precursor, this method demonstrates incredible efficiency in just 45 min. In the presence of methanol, our method results in formation of predominantly bi-layer graphene, which is more difficult to obtain in scalable fashion, than mono-layer graphene. The high quality of as-obtained graphenes is fully confirmed by Raman spectroscopy, TEM, SAED, AFM and X-ray photoelectron spectroscopy.